Chosen health behaviors about cancer prevention among sanok district residents and sociodemographic variables – preliminary study - Smoleń, Ewa; Cipora, Elżbieta; Hombek, Karolina; Jarema, Magdalena (Journal of Education, Health and Sport, 2017)
Indtroduction. Eliminating risk factors and creating health habits are essential elements for improving the health of the population, thereby reducing morbidity and mortality caused by cancer. Aim. Defining some health .habits in relation to risk factors for cancer among the inhabitants of Sanok district Material and methods. The study was conducted among 157 residents of Sanok district in 2015. The method used was a diagnostic survey, and as research tools were used an author questionnaire and Health Behavior Inventory adapted by Z. Juczyński. Results. Most of the respondents received a low level of health behavior. Almost half of the respondents were diagnosed with at least one type of cancer in the family. Most of them were breast, lung and pancreas cancer. Almost one third of respondents performed screening. The main reason for doing this study was to diagnose early stage of cancer so that to enable effective treatment. As the main reasons for avoiding participation in preventive tests, the respondents pointed to their well-being and lack of time. More than three-quarters of respondents did not observe any disturbing changes on the skin, whereas among the rest of the respondents the most frequent change was a mole. Only every tenth respondent took advantage of a visit to the oncologist for a prevention test and most were people above 70 years of age. Conclusions. Age, gender, education and place of residence to a different degree diversified health behaviors in the study group. One of the non-modifiable risk factors for cancer observed among the respondents was the occurrence of cancer in the family, and unwanted behavior that posed a potential risk factor was avoiding screening.